Hubungan Literasi Ekologi (Ecological Literacy) Terhadap Sikap Peduli Lingkungan Peserta Didik di Sekolah Adiwiyata - Lestari, Cahya; Nisa, Jakiatin; Ardiansyah, Andri Noor (Sosio-Didaktika: Social Science Education Journal, 2025)
This study aims to analyze the relationship between ecological literacy and the environmental awareness of students at SMAN 28 Jakarta Adiwiyata School. The research method used a survey with a quantitative approach and statistical analysis. The population in this study was all students in grades XI and XII, with a sample size of 84 students using stratified random sampling. Data collection techniques used tests and questionnaires. Based on the results of ecological literacy testing, it was found that the correlation coefficient value was 0.717. This correlation coefficient is positive, indicating a meaningful unidirectional relationship. That is, high ecological literacy values will also increase students' environmental awareness, which is measured based on attitudes towards energy, air, the social environment, flora and fauna, and waste management. The results of the simple linear regression test show that there is a significant influence between ecological literacy and students' environmental awareness, with a coefficient of determination of 0.514, which means that the influence of the ecological literacy variable on environmental awareness is 51.4%, while 48.6% is determined by other variables. These findings form the basis for strategic recommendations for the management of Adiwiyata Schools and education policymakers to continue developing effective environmental literacy programs that support environmental sustainability through character building and shaping students' attitudes. Keywords: Ecological Literacy, Students' Environmental Attitudes, Adiwiyata Schools